(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
In recent years, the quality of cereal flour, as well as rye flour, has changed due to a decrease in biologically valuable components. This can be attributed to climatic conditions, modern technologies of grain cultivation and processing. The baking properties of flour depend on the state of carbohydrate-amylase and protein-proteinase complexes. Rye flour proteins, unlike wheat proteins, do not form a gluten network. For a long time, it was believed that they were not capable of forming gluten. However, it can be extracted in weak solutions of salts or organic acids. The yield of raw gluten is 5-10%. The role of the protein-proteinase complex in forming the structural and mechanical properties of dough is reduced to the formation of a viscous colloidal solution in it, which gives the dough plasticity. The carbohydrate-amylase complex of rye flour also has its own characteristics. Rye flour has a high content of the natural sugars. Starch polysaccharides amylose and amylopectin are more easily hydrolytically split by the amylolytic enzymes. The purpose of the article is to evaluate the quality of rye grown in Ukraine and to investigate the baking value of rye flour presented on the market for the further development of technological solutions for expanding the assortment of rye flour. Rye quality assessment of the 2022-2023 harvest has shown that all samples meet the requirements of DSTU 4522:2006 Rye. Technical specifications. Research on the baking quality of rye flour indicates different values of protein (5.8-6.9%), ash content (1.1-1.27%), falling number (186-230 s), damaged starch (14.6-18,3 UCD), water absorption capacity (63.0-65.4%). Such discrepancies in the values of the indicators of different producers of rye flour indicate a great difference in the quality of raw materials used in processing, a difference in the construction of the technological process and the operating modes of basic technological operations. In connection with the above-mentioned, it is promising to continue researching the quality of rye flour from factories of different productivity, as well as to evaluate the quality of flour of individual streams for the possibility of establishing a stable quality of rye flour or selecting flour with special properties.